A case of syngeneic graft-versus-host disease. (October 2019) - Patel, Sweta U; Yum, Kendra; Kim, Sara; Isola, Luis M; Scigliano, Eileen; Jakubowski, Rita; Park, Doyun
Graft-versus-host disease has been reported to occur rarely in syngeneic hematopoietic stem cell transplant recipients. Clinical and histological changes consistent with graft-versus-host disease have been reported to occur in this patient population. We report a case of a 46-year-old Caucasian male with diffuse large B-cell lymphoma in complete remission who underwent a syngeneic hematopoietic stem cell transplant. He was diagnosed with grade III acute skin and gastrointestinal graft-versus-host disease requiring high-dose corticosteroids and immunosuppressive therapy and resulting in a complete response. Syngeneic graft-versus-host disease is an anomaly that needs to be considered as a differential diagnosis of patients experiencing dermatitis, gastroenteritis, or hepatitis after an identical twin hematopoietic stem cell transplant.